(untitled) (Academicia Globe: Inderscience Research, 2023)
We collected 120 urine samples, and 28 (23.3%) of these samples included E. coli isolates. The isolates’ susceptibilities to antibiotics varied. It was determined that every sample was incredibly resistant to both beta-lactam and non-beta-lactam antibiotics., although all isolates were resistant to imipenem .